2016
DOI: 10.1515/chempap-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activities of novel quinazolinone derivatives containing a 1,2,4-triazolylthioether moiety

Abstract: A series of novel quinazolinone derivatives containing a 1,2,4-triazolylthioether moiety were synthesised and their antimicrobial activities were evaluated. All the target compounds were characterised by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Compared with some of the arylimine derivatives containing the 3-aminoethyl-2-[(p-triuoromethoxy)anilino]-4(3H)-quinazolinone moiety reported by Song et al, 24 compounds 7e, 7g and 7n had weaker but comparable activities against the Xoo on the basis of their EC 50 values. Notably, relative to some quinazoline derivatives containing the 1,2,4-triazolylthioether moiety reported by our group, 16 the above three compounds exhibited signicantly better antibacterial activities against the Xoo.…”
Section: Antibacterial Activitymentioning
confidence: 62%
See 1 more Smart Citation
“…Compared with some of the arylimine derivatives containing the 3-aminoethyl-2-[(p-triuoromethoxy)anilino]-4(3H)-quinazolinone moiety reported by Song et al, 24 compounds 7e, 7g and 7n had weaker but comparable activities against the Xoo on the basis of their EC 50 values. Notably, relative to some quinazoline derivatives containing the 1,2,4-triazolylthioether moiety reported by our group, 16 the above three compounds exhibited signicantly better antibacterial activities against the Xoo.…”
Section: Antibacterial Activitymentioning
confidence: 62%
“…In 1999, the ndings made by Kung et al indicated that both quinazoline ring and piperidinyl linker in target compounds were indespensible for achieving effective antibacterial activities. 15 Based on the above-mentioned considerations and our continuing interest in the development of 1,2,4-triazole-quinazoline/ quinazolinone hybrid derivatives as effective antimicrobial agents, [16][17][18][19][20] herein we introduced various N-(substituted phenyl) acetamide groups into quinazolinylpiperidinyl-modied 1,2,4-triazole ring ( Fig. 2) and evaluated their inhibition activities against some important phytopathogenic bacteria and fungi.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Yan and coworkers [38] reported a series of novel thioether derivatives containing a 1,2,4triazolylthioether moiety and their in vitro antifungal activities against G. zeae, C. mandshurica, P. infestans, P. sasakii, C. capsici, and G. fructigenum were evaluated. Bioassay results showed that compound 27 (Figure 6) exhibited better fungicidal activities against P. sasakii (65.9%) and C. capsici (65.1%) at 50 μg/mL in comparison with those of Hymexazol.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Quinazolin-4-ol (1) was prepared as described in the literature, [31] Upon refluxing with freshly distilled thionyl chloride in presence of catalytic amount of DMF, compound 1 yielded the corresponding 4-chloro derivative 2 [32]. Which followed by its reaction with sodium azide in DMF to give 4-azidoquinazoline 3 Quinazolone derivatives bearing different moieties for example hydrazide, ester, or imine derivatives at the N-3 position are well known to exhibit powerful antimicrobial activities [33][34][35]. In this context, our main target was dedicated at the design and the synthesis of novel series of N-3 substituted quinazolone derivatives according to the synthetic methods showed in (Scheme 2).…”
Section: Ethyl 5-amino-1-(quinazolin-4-yl)-1h-pyrazole-4-carboxylate mentioning
confidence: 99%